Self-Concept as a Mediator in the Relationship between TikTok @_Project.xo Social Media Usage and Psychological Well-being of Generation Z - Oka Rasidian; Zakki Nurul Amin (Indonesian Journal of Guidance and Counseling: Theory and Application, 2025)
This study examines the role of self-concept as a mediator in the relationship between TikTok @_Project.xo usage and psychological well-being among Generation Z in Indonesia using PROCESS Macro analysis. The focus of this study is to deepen the theoretical understanding of the internal mechanisms linking social media engagement and psychological well-being. Collect a quantitative approach with a descriptive-correlative design from 150 Generation Z respondents selected through purposive sampling. Data were collected using three standardized instruments: the Social Media Engagement Scale for Adolescents (SMES-A), the Robson Self Concept Questionnaire, and the Ryff Psychological Well-Being Scale (18 items). The analysis shows that self-concept significantly mediates the relationship between TikTok usage and psychological well being (β = 0.057; 95% CI = 0.022–0.094). TikTok usage does not have a direct effect on psychological well-being, but has an indirect effect through self-concept. This indicates that self-concept serves as a full mediator. These findings enrich the literature on the psychological well-being of Generation Z in Indonesia and open up further research directions to explore other mediator or moderator variables.